Research for the application and safety of MD5 algorithm in password authentication - Xiaoling Zheng; Jidong Jin (2012 9th International Conference on Fuzzy Systems and Knowledge Discovery, 2012)
MD5 algorithm takes an important position in the application of password authentication. This essay analyses the security features of the passport authentication and the methods of application safety improvement of MD5 algorithm in password authentication, on the basis of which, it focuses on the methods of the application safety improvement of MD5 in the passport authentication by switching or interfering with the treatment process of MD5.